Synthesis, photophysical characterisation and photostability studies of NIR probes with aliphatic, aromatic and chlorinated terminals in 5- and 9-amino positions of benzo[a]phenoxazines - Raju, B. Rama (2016)
A new series of benzo[a]phenoxazinium chlorides possessing mono- or disubstituted amines with 3-chloropropyl groups at the 9-position, isopropyl, cyclohexyl and phenyl groups as terminals at 5-postion was synthesised. Photophysical studies were performed in dry ethanol and aqueous solutions. The terminals at the 5-amino position were found to influence the acid-base equilibrium. The presence of hydroxyl functionality at 2-position was found to introduce an additional basic form that is the one in equilibrium with the cationic acid form in dry ethanol solutions. The photostability of these compounds in different media was also investigated and a high resistance to photobleaching in model biological membranes was observed. In proteins a moderate of 20% photobleaching occurs in 1h 30min, while in water more than 60% of the compound molecules are photodegraded during the same time interval.